Adjuvant interventions with opioids for vaso-occlusive crisis in sickle cell disease: A mixed treatment network meta-analysis of randomized controlled clinical trials - Sridharan, MD, DM, Kannan; Sivaramakrishnan, MDS, Gowri (Journal of Opioid Management, 2020)
Objective: Vaso-occlusive crisis is the most common clinical feature requiring opioid analgesics in patients with sickle cell disease. We conducted a network meta-analysis to compare the drugs that can be used as add-on with opioids for vaso-occlusive crisis. Design: Network meta-analysis of randomized clinical trials. Patients: Sickle cell disease patients with vaso-occlusive crisis receiving adjuvants to opioids for pain management. Main outcome measures: A number of patients with complete pain relief and pain scores assessed either by visual analog or by a numerical rating scale were the primary outcomes. Adverse events and dose of opioids (in morphine equivalents) for pain alleviation between the treatment arms were the secondary outcome measures. Results: Eleven studies evaluating the addition of ketorolac, magnesium sulfate, ketoprofen, ibuprofen, methadone, inhalational nitric oxide, methylprednisolone, and arginine with morphine were obtained. The pooled analysis showed a favorable effect in the pain reduction for the additions of arginine {–2 [–3.39, –0.61]} and ibuprofen {–1.7 [–3.26, –0.14]} with morphine. Arginine has high probability of being the “best” in the pool followed by ibuprofen. No significant differences were observed in the risk of adverse events {ketoprofen—0.84 [0.42, 1.65]; magnesium sulfate—1.81 [0.64, 5.81]; and arginine—2.08 [0.18, 24.31]}. A significant lower dose of opioid was required when given adjunctive to arginine, inhalational nitric oxide, and methylprednisolone. Conclusion: We observed that arginine and ibuprofen could produce additional analgesic effects when combined with morphine in vaso-occlusive crisis.